2022
DOI: 10.3390/life12030415
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Pathways in the Genesis of Plasmodium-Derived Microvesicles: A Double-Edged Sword?

Abstract: Malaria, caused by Plasmodium species (spp.), is a deadly parasitic disease that results in approximately 400,000 deaths per year globally. Autophagy pathways play a fundamental role in the developmental stages of the parasite within the mammalian host. They are also involved in the production of Plasmodium-derived extracellular vesicles (EVs), which play an important role in the infection process, either by providing nutrients for parasite growth or by contributing to the immunopathophysiology of the disease.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…This confirms that parasite activated the dose-dependent autophagy to circumvent the anti-plasmodial defenses. The gene transcription profiling of P. berghei (pathogen) and mice (host) further suggested that the activation of autophagy-like escape mechanism evading the anti-plasmodial defenses could be a double-edged sword 6 ( Figures 10 B and 10C). Autophagy helped parasite escape the anti-plasmodial defenses and withstand drug pressure to confer the extended survival by inhibiting the programmed cell death ( Figures 4 and 10 C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This confirms that parasite activated the dose-dependent autophagy to circumvent the anti-plasmodial defenses. The gene transcription profiling of P. berghei (pathogen) and mice (host) further suggested that the activation of autophagy-like escape mechanism evading the anti-plasmodial defenses could be a double-edged sword 6 ( Figures 10 B and 10C). Autophagy helped parasite escape the anti-plasmodial defenses and withstand drug pressure to confer the extended survival by inhibiting the programmed cell death ( Figures 4 and 10 C).…”
Section: Discussionmentioning
confidence: 99%
“…Oleuropein (OLP) possessing anti-inflammatory, anti-oxidants, immunomodulatory activity is known to activate autophagy. 5 , 6 , 7 , 8 Hence. human THP-1 macrophage model of inflammation (MMI; antigen [LPS]-stimulated macrophages) was developed to confirm the inflammatory and signaling properties of OLP.…”
Section: Introductionmentioning
confidence: 93%
“…However, experiments with null-VAR2CSA parasites were missing so we cannot rule out the hypothesis that observed effects might still occur in a binding independent manner and simply due to parasite antigen recognition. Plasmodium -derived microvesicles, which carry parasite-derived antigens and activate the immune system, are transferred to astrocytes by LC3-associated phagocytosis, with implications to neuroinflammation and cerebral malaria pathogenesis ( 91 ). Besides, microvesicles can also trigger inflammation by activating TLR4-MyD88 axis ( 92 ), which is linked to autophagy modulation as previously discussed.…”
Section: Is There a Role For Placental Autophagy In Mip?mentioning
confidence: 99%